Dilemmas of Diaspora: Partition, Refugees, and the Politics of “Home” - Bose, Pablo (Refuge: Canada’s Journal on Refugees, 2006)
The following paper explores the idea of “refugee diasporas” by focusing on a case study of the Hindu Bengali exodus from East Pakistan (later Bangladesh) following the 1947 British Partition of India. The author begins by problematizing and historicizing definitions of diasporas in general and refugee diasporas in particular and then uses the case study to illustrate the diversity in experiences that different groups that emerged from the Partition encountered. This focus on the lived experiences of flight, resettlement, integration (or lack thereof), and the rebuilding of lives helps to unravel some of the embedded and obscured meanings that terms such as “refugee diaspora” might otherwise contain.